1984
DOI: 10.1063/1.333021
|View full text |Cite
|
Sign up to set email alerts
|

Formation of thin films of NiSi: Metastable structure, diffusion mechanisms in intermetallic compounds

Abstract: The formation of NiSi films from the reaction of Ni2Si with (100) and (111) silicon substrates was found to be controlled by a lattice diffusion process with an activation energy of 1.70 eV. In order to correlate kinetic information obtained by Rutherford backscattering with x-ray diffraction data, ‘‘standard’’ diffraction powder patterns for both Ni2Si and NiSi have been established. The existence of a metastable hexagonal form of NiSi has been confirmed. Observations on the formation of Ni2Si confirm previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(87 citation statements)
references
References 32 publications
8
78
1
Order By: Relevance
“…These observed results correspond to what is known from literature. 20 Adding Pd changes the reaction sequence significantly, as can be inferred from Figs. 1(b)-1(d) showing the in situ XRD measurements on 45 nm Ni(Pd) films containing 5%, 10%, and 15% of Pd, respectively.…”
Section: Resultssupporting
confidence: 48%
“…These observed results correspond to what is known from literature. 20 Adding Pd changes the reaction sequence significantly, as can be inferred from Figs. 1(b)-1(d) showing the in situ XRD measurements on 45 nm Ni(Pd) films containing 5%, 10%, and 15% of Pd, respectively.…”
Section: Resultssupporting
confidence: 48%
“…The growth of the first two phases is reported to be diffusion controlled, with Ni as dominant diffusing species [17,18]. NiSi 2 on the other hand is a phase of high resistivity that nucleates at temperatures above 800 ○ C [10,19].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the large difference in mobility between Si and the RE element leads to pinhole formation, which is detrimental for dedicated electrical contacts [9]. Ni silicides (Ni 2 Si and NiSi) on the other hand grow via a diffusion controlled growth mechanism in which the metal is the DDS [10,11]. As such, the combination of both mechanisms in one system makes ternary Ni-RE silicide thin film growth appealing to study fundamental processes in thin film solid phase reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For the non-cubic phases, such as TiSi 2 and NiSi, an epitaxial match between film and substrate is less obvious. Based on X-ray diffraction measurements in Bragg-Brentano geometry, it was concluded that these materials exhibit a random texture [7]. Indeed, lots of peaks, belonging to different planes, show up, indicating that not one single specific plane is parallel to the substrate.…”
Section: Texture Of Silicidesmentioning
confidence: 99%